University textbook on oral mucosal diseases - Izakovičová Hollá, Lydie (Masaryk University Press, 2020)
This textbook is primarily intended for students of dental medicine, it can also be useful for the students of general medicine whom it can help in clinical and field practice. The term "diseases of the oral mucosa" describes a diverse group of diseases of various aetiologies and seriousness and this issue is closely related to dermatovenerological, otorhinolaryngological, ophthalmological, rheumatological and internal diseases. The dentist may often be the first physician noticing and possibly diagnosing a general disease based on symptoms of the oral cavity. The new extended edition reflects the improving knowledge of the etiopathological processes of oral mucosal diseases on the molecular level and the ever increasing range of diagnostic laboratory tests and/or therapeutic options.